Iron‐Catalyzed Olefin Metathesis: Recent Theoretical and Experimental Advances. Issue 62 (8th September 2022) - Grau, Benedikt W.; Neuhauser, Alexander; Aghazada, Sadig; Meyer, Karsten; Tsogoeva, Svetlana B.
Abstract: The "metathesis reaction" is a straightforward and often metal‐catalyzed chemical reaction that transforms two hydrocarbon molecules to two new hydrocarbons by exchange of molecular fragments. Alkane, alkene and alkyne metathesis have become an important tool in synthetic chemistry and have provided access to complex organic structures. Since the discovery of industrial olefin metathesis in the 1960s, many modifications have been reported; thus, increasing scope and improving reaction selectivity. Olefin metathesis catalysts based on high‐valent group six elements or Ru(IV) have been developed and improved through ligand modifications. In addition, significant effort was invested to realize olefin metathesis with a non‐toxic, bio‐compatible and one of the most abundant elements in the earth′s crust; namely, iron. First evidences suggest that low‐valent Fe(II) complexes are active in olefin metathesis. Although the latter has not been unambiguously established, this review summarizes the key advances in the field and aims to guide through the challenges. Abstract : Iron‐catalyzed olefin metathesis is high on the list of existing challenges in chemistry. Iron is one of the most abundant elements in the earth's crust, and, therefore, iron catalysts would offer highly attractive alternatives to Ru‐ and Mo‐based catalysts. This Review summarizes the key recent theoretical and experimental advances towards the development of iron‐catalyzed olefin metathesis.